Epitaxial Metal Halide Perovskites by Inkjet‐Printing on Various Substrates. (4th September 2020) - Sytnyk, Mykhailo; Yousefi‐Amin, Amir‐Abbas; Freund, Tim; Prihoda, Annemarie; Götz, Klaus; Unruh, Tobias; Harreiss, Christina; Will, Johannes; Spiecker, Erdmann; Levchuk, Jevgen; Osvet, Andres; Brabec, Christoph J.; et al.
Abstract: Metal‐halide‐perovskites revolutionized the field of thin‐film semiconductor technology, due to their favorable optoelectronic properties and facile solution processing. Further improvements of perovskite thin‐film devices require structural coherence on the atomic scale. Such perfection is achieved by epitaxial growth, a method that is based on the use of high‐end deposition chambers. Here epitaxial growth is enabled via a ≈ 1000 times cheaper device, a single nozzle inkjet printer. By printing, single‐crystal micro‐ and nanostructure arrays and crystalline coherent thin films are obtained on selected substrates. The hetero‐epitaxial structures of methylammonium PbBr3 grown on lattice matching substrates exhibit similar luminescence as bulk single crystals, but the crystals phase transitions are shifted to lower temperatures, indicating a structural stabilization due to interfacial lattice anchoring by the substrates. Thus, the inkjet‐printing of metal‐halide perovskites provides improved material characteristics in a highly economical way, as a future cheap competitor to the high‐end semiconductor growth technologies. Abstract : Epitaxial growth of metal‐halide‐perovskites (MHP) is demonstrated by inkjet printing, which can enable further improvements in perovskite thin‐film devices by achieving structural coherence on the atomic scale. Single‐crystal micro‐arrays and crystalline coherent thin films are obtained on selected substrates. The MHP hetero‐epitaxial structures exhibit bright luminescence and extended cubic crystal phase stability due to interfacial lattice anchoring by the substrates.